A Comparative Analysis of Personal Data Protection Laws in Indonesia and Vietnam - Septian Khairuddin; Akhmad Safik (al Hairy | Journal of Islamic Law, 2026)
Personal data protection is an important issue in the digital era marked by the massive use of information technology. This study compares the rationality of personal data protection in Indonesia and Vietnam through Law No. 27 of 2022 and Decree No. 13/2023/ND-CP.  Both regulations are present in response to the increasing need or urgency for personal data protection in ASEAN, especially Indonesia and Vietnam. The aim is to understand the rational and background in the formation of both regulations, by analyzing the juridical, sociological, and philosophical aspects. The results show that although both countries face the same challenges as the rise of personal data leaks, there are fundamental differences in the legal approach used. Indonesia governs through laws with a high legal standing and oversight by independent institutions, while Vietnam governs through decrees (Nghị định) which are under the law (Luật) or are directly controlled by the government through the Bộ Côngan or the Ministry of Public Security. Indonesia's philosophical approach is rooted in human rights and social justice, while Vietnam's emphasizes more on national stability and security. This research shows the importance of personal data regulation that is not only legally strong, but also in accordance with the social and cultural values of each country to realize a safe and fair society.